2016
DOI: 10.2147/ijn.s111950
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of pH-sensitive copolymer micelles with tumor-specific peptide for enhanced cellular uptake of doxorubicin

Abstract: To improve the targeting efficacy of hyaluronic acid (HA)-based micelles, pH-sensitive mixed micelles based on HA-g-poly(L-histidine) (PHis) and d-α-tocopheryl polyethylene glycol 2000 copolymers were prepared and decorated with human epidermal growth factor receptor 2 (Her2) peptide, a tumor cell-specific peptide ligand, on their surface. The doxorubicin-loaded micelles (HA-PHis/peptide–d-α-tocopheryl polyethylene glycol 2000 mixed micelles [PHTM]) were characterized to have a unimodal size distribution and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Our results are consistent with research by Chen et al, which used specific inhibitors of endocytosis to assess the cellular uptake of micelles decorated with the same Her2-binding peptide. 30 The receptor-mediated endocytosis, both clathrin-and caveola-mediated, is the predominant pathway of micelle entry into cells. 30 Moreover, Chen et al indicated that macropinocytosis was not closely involved in the internalization of these particles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are consistent with research by Chen et al, which used specific inhibitors of endocytosis to assess the cellular uptake of micelles decorated with the same Her2-binding peptide. 30 The receptor-mediated endocytosis, both clathrin-and caveola-mediated, is the predominant pathway of micelle entry into cells. 30 Moreover, Chen et al indicated that macropinocytosis was not closely involved in the internalization of these particles.…”
Section: Discussionmentioning
confidence: 99%
“…30 The receptor-mediated endocytosis, both clathrin-and caveola-mediated, is the predominant pathway of micelle entry into cells. 30 Moreover, Chen et al indicated that macropinocytosis was not closely involved in the internalization of these particles. 30 EGF receptors utilize multiple endocytotic pathways, possibly depending upon the ligand type and its concentration in the extracellular milieu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(amino acids) are the most common enzymatically degradable polymers which are conjugated to HA for the fabrication of nanocarriers [28,29,30,35,57,58,59,60]. Lecommandoux et al used poly(benzyl- l -glutamate) (PBLG) for the synthesis of HA-based polymersomes (Figure 3) with a size around 200 nm to convey different chemotherapeutic drugs such as DOX [29,30] and docetaxel (DOC) [28], with a high drug loading capacity (see Table 1).…”
Section: Nanocarriers Based On Ha-polymers Conjugates: Biomedical mentioning
confidence: 99%
“…According to the enhanced permeability and retention (EPR) effect, nanocarriers have passive targeting property (tend to enter tumors from irregular microvasculature and stay there for a longer period than small molecule drugs) [ 42 , 43 ]. Equipped with targeting ligands, nanocarriers are imparted with active targeting property (tend to actively accumulate in specific tumor tissues), reducing systematic toxicity and enhancing therapeutic effects [ 44 , 45 ]. Moreover, if triggered by external stimuli within tumor tissues or cells, nanocarriers may release the loaded drugs, directly exerting antitumor effects [ 43 , 46 ].…”
Section: The Basics Of Polymer-based Nanocarriersmentioning
confidence: 99%